Les séries télé des networks américains - Mathieu de Wasseige (Communication)
In order to achieve commercial success, the television series broadcast on major US networks during the past decade must play an “ideological balancing game.” To illustrate how this game is played, the author compares Desperate Housewives with Grey’s Anatomy, and C.S.I. : Crime Scene Investigation with Cold Case. The act of ideological balancing in all four series takes place in the narrative that ensures a proportional distribution in the story lines of current social issues, even those that are particularly sensitive.